Accountability and Transparency of Hajj Fund Financial Management: A Bibliometric Analysis - Maysyaroh, Siti; Pratiwi Ch, Siti Angelina; Mawaddah; Saputri, Sukma Winnata; Humairah, Andi; Khomsatun, Siti (SMART Insight, 2024)
This paper aims to explore the accountability and transparency of Hajj fund management through bibliometric analysis and data examination. This study uses paper publication data sourced from various research journals on the theme of Hajj fund management. The data was collected within the last 10 years. As a result, there were 103 publications related to the theme of